Incidence and predictors of delirium on the intensive care unit after acute myocardial infarction, insight from a retrospective registry. Issue 6 (14th September 2020) - Jäckel, Markus; Zotzmann, Viviane; Wengenmayer, Tobias; Duerschmied, Daniel; Biever, Paul M.; Spieler, Derek; von zur Mühlen, Constantin; Stachon, Peter; Bode, Christoph; Staudacher, Dawid L.
Abstract: Objectives: This study aimed to identify the incidence and potential risk factors for delirium after myocardial infarction (MI). Background: Delirium is a common complication on intensive care units. Data on incidence and especially on predictors of delirium in patients after acute MI are rare. Methods: In this retrospective study, all patients hospitalized for MI treated with coronary angiography in an university hospital in 2018 were included and analyzed. Onset of delirium within the first 5 days after MI was attributed to the MI and was defined by a Nursing Delirium screening scale (NuDesc) ≥2. This score is taken as part of daily care in every patient on intensive care unit three times a day by especially trained nurses. Results: A total of 624 patients with MI (age 68.5 ± 13.2 years, ST‐elevation MI 41.6%, hospital mortality 3.2%) were included in the study. Delirium was detected in 10.9% of all patients. In the subgroup of patients with a stay on the intensive care unit (ICU) for more than 24 hr ( n = 229), delirium was detected in 29.7%. Hospital and ICU stay were significantly longer in patients with delirium ( p < .001). Delirium was an independent predictor of prolonged ICU‐stay. Independent predictors of delirium were age, dementia, alcohol abuse, cardiac arrest, hypotension, and leucocytosis. Infarct size or presentation with ST‐elevation were not associated with incidence of delirium. Conclusion: Development of delirium is frequent after acute MI and prolongs hospitalization. Incidence of delirium is associated with clinical instability, preexisting comorbidity, and age rather than MI type or size.